Nanosized Ferric Hydroxide Catalyzed C-O Cross-Coupling of Phenol and Halides to Generate Phenoxy Ether - Sun, Hongbin; Sun, Yuanhua; Tian, Xiaohua; Zhao, Yunxia; Qi, Xuan (Asian Journal of Chemistry, 2013)
The iron-based catalyst can effectively catalyze the phenolic hydroxyl C-O bond formation reaction to give the corresponding phenoxy ethers. The reaction of phenol and methyl chloroacetate, for example, gives phenoxy acetic acid methyl ester in 98 % yield under the optimal reaction conditions. Among the iron-based catalysts, nanosized ferric hydroxide prepared through sol-gel method gives the best catalytic activity.